2019
DOI: 10.3390/nu11051098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mediterranean Dietary Patterns During Pregnancy on Maternal and Offspring Health

Abstract: (1) Background: Pregnancy outcomes for both mother and child are affected by many environmental factors. The importance of pregnancy for ‘early life programming’ is well established and maternal nutrition is an important factor contributing to a favourable environment for developing offspring. We aim to assess whether following a Mediterranean Diet during pregnancy is beneficial for maternal and offspring outcomes; (2) Methods: a systematic review was performed using standardized reporting guidelines with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 48 publications
2
87
2
1
Order By: Relevance
“…13,14 This study retrospectively analyzed the exposure of common risk factors in mothers' living and working environment one year before and after pregnancy, and assessed the risk of developing fetal congenital heart disease. 15 The results indicated that maternal medication in early pregnancy, viral infection, hair dyeing and perm during pregnancy or half a year before pregnancy, house decoration, parents' exposure to environmental pollution are independent risk factors for congenital heart disease in infants and young children. [16][17][18] Multivariate logistic regression analysis showed that the incidence of CHD was associated with hair perm and dyeing, medication taken by mothers in early pregnancy, house decoration, virus infection, and exposure to pollution of working environment.…”
Section: Discussionmentioning
confidence: 96%
“…13,14 This study retrospectively analyzed the exposure of common risk factors in mothers' living and working environment one year before and after pregnancy, and assessed the risk of developing fetal congenital heart disease. 15 The results indicated that maternal medication in early pregnancy, viral infection, hair dyeing and perm during pregnancy or half a year before pregnancy, house decoration, parents' exposure to environmental pollution are independent risk factors for congenital heart disease in infants and young children. [16][17][18] Multivariate logistic regression analysis showed that the incidence of CHD was associated with hair perm and dyeing, medication taken by mothers in early pregnancy, house decoration, virus infection, and exposure to pollution of working environment.…”
Section: Discussionmentioning
confidence: 96%
“…More interestingly, the influence of certain factors related to both asthma and obesity seem to be important during pregnancy or during the first weeks of life. For instance, adherence to a Mediterranean diet by the mother in pregnancy seems to have implications for both asthma and obesity [20]. Moreover, maternal obesity in pregnancy is associated to both asthma and obesity in the offspring [21,22].…”
Section: Diet and The Parallel Epidemics Of Obesity And Asthmamentioning
confidence: 99%
“…It is characterized by a high intake of whole foods, fruits, vegetables, whole grain cereals, legumes, fish, and nuts and extra-virgin olive oil, low-to-moderate consumption of dairy products, smaller amounts of white meat and red wine, and a minimal consumption of processed food, red meat, animal fats, and sugar [ 3 ]. In this context, the beneficial effects of the Mediterranean diet on the mother’s health during gestation, as well as the importance of maternal health for the child later in life has been well established [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. However, the influence of the maternal diet is also interlinked with many other lifestyle factors, including smoking, body mass index (BMI), education, age, urban versus rural residency etc., [ 11 ].…”
Section: Introductionmentioning
confidence: 99%